KERAJINAN COR LOGAM ALUMINIUM SEGOROYOSO PLERET BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Timbul Raharjo; Joko Subiharto (Institut Seni Indonesia Yogyakarta, 2017)
The cast aluminum products at Karanggayam, Segoroyoso, Pleret, Bantul is suffering from quality stagnation. They are limited to manufacturing